Tangible and intangible assets in the growth performance of the EU, Japan and the US - Amat Adarov; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2019)
This paper discusses new results using the EU KLEMS 2019 Release focussing on the role of ICT and intangibles assets employing a growth accounting framework and an econometric analysis. The EU KLEMS 2019 data covers most EU Member States, the US and Japan, forty detailed industries according to NACE Rev. 2 (ISIC Rev. 4) along with nine aggregated industries and spans over the period 1995-2017. In particular, intangible assets outside the boundaries of the national accounts are taken into account. The data are used to study total factor productivity, labour and capital productivity developments in a comparative cross-country and cross-industry dimension with an emphasis on the role of capital investments. Inter alia, the analysis studies the implications of various asset types and particularly the role of ICT and intangible capital, as well as changes in labour services and the composition thereof, as drivers of value added and labour productivity growth. Significant differences in the underlying growth contributions between the pre-crisis and post-crisis periods in growth performances are highlighted.
Keywords: C82; D24; O47; 330; EU KLEMS; growth accounting; tangible and tangible assets; ICT and non-ICT capital; productivity and growth